Development of hypnoteaching-based learning videos to improve learning outcomes of IPAS materials: "Let's get acquainted with our earth" grade V students - Warto; Achmad Buchori; Ngatmini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aimed to develop hypnoteaching-based learning media to enhance fifth-grade students' learning outcomes in Natural and Social Sciences (IPAS – a subject that integrates natural and social science content in the Indonesian elementary curriculum) using the ADDIE model. Conducted in a public elementary school in Central Java, the study employed expert validation, observation, student response questionnaires, and learning outcome tests. Data were analyzed using descriptive statistics and paired-sample t-tests. Results showed excellent validity (average expert rating = 4.7) and a significant improvement in scores from the pre-test (60.00) to the post-test (70.26), with an N-Gain of 0.26, categorised as low based on Hake's criteria. The media received a positive response from students (average satisfaction score = 4.2). Despite the low N-Gain, the hypnoteaching-based media proved to be a practical and engaging tool. Future integration with broader educational technologies is recommended.